The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1080/02615479.2016.1185407
|View full text |Cite
|
Sign up to set email alerts
|

The role of practice educators in initial and post qualifying social worker education

Abstract: Doctoral research into competence for social work practice engaged with seventeen participants who drew upon their experiences of being practice educators and registered social work practitioners and the analysis of data suggested they identified a difference between competence to pass a final placement and capability for social work practice. Baseline social work knowledge, skills and values will enable a student to pass a final placement however, research data suggests that the individual's approach to learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Higher emotional intelligence is one of the resilient factors for preventing burnout in social service workers. For example, research has found that of emotional intelligence was negatively related with their level of burnout for marriage and family counselors burnout (Gutierrez & Mullen, 2016) and social workers (Stone, 2016). Similarly, research about burnout among similar professionals has shown a negative correlation between burnout and emotional intelligence among doctors (Swami et al, 2013) and teachers (Mérida-López & Extremera, 2017).…”
Section: Emotional Intelligencementioning
confidence: 99%
“…Higher emotional intelligence is one of the resilient factors for preventing burnout in social service workers. For example, research has found that of emotional intelligence was negatively related with their level of burnout for marriage and family counselors burnout (Gutierrez & Mullen, 2016) and social workers (Stone, 2016). Similarly, research about burnout among similar professionals has shown a negative correlation between burnout and emotional intelligence among doctors (Swami et al, 2013) and teachers (Mérida-López & Extremera, 2017).…”
Section: Emotional Intelligencementioning
confidence: 99%
“…Practice education, as a vital cog of such expansive practice learning, can be considered underused, when, if effectively supported, it can support deep and critically reflective learning within social work organisations from student through to experienced and advanced practitioner levels (Stone, 2016;Nixon and Murr, 2006). A range of scholars (Bogo et al 2002;Parker, 2007;Regehr et al, 2002) suggest that ongoing, stable and effective support, critically reflective and educative supervision, and forums for group and peer learning are critical to good practice education.…”
Section: Introductionmentioning
confidence: 99%
“…Existing research into social work practice education is rather limited but includes for example the use of assessment frameworks (Stone, 2014b) and the use of performance measures to assess outcomes in student learning and assessment (Cleak, Hawkins, Williams, & Laughton, 2015). The important role practice educators can play in initial social work education has been explored (Stone, 2016) and also the reasons why they may be reluctant to fail students (Finch, 2009;Finch & Parker, 2013;Finch & Taylor, 2012). Research has considered the relationship between supervision quality and student satisfaction (Kanno & Koeske, 2010); relationships between students and practice educators (Lefevre, 2005;Zeira & Schiff, 2014); and attention has been drawn to strategies practice educators may employ to reduce anxiety in students (Baird, 2016).…”
Section: Introductionmentioning
confidence: 99%